The CMV-encoded G protein-coupled receptors M33 and US28 play pleiotropic roles in immune evasion and alter host T cell responses - White, Timothy M.; Bonavita, Cassandra M.; Stanfield, Brent A.; Farrell, Helen E.; Davis-Poynter, Nicholas J.; Cardin, Rhonda D. (Frontiers in Immunology, 2022)
Introduction Human cytomegalovirus (HCMV) is a global health threat due to its ubiquity and lifelong persistence in infected people. During latency, host CD8+ T cell responses to HCMV continue to increase in a phenomenon known as memory inflation. We used murine CMV (MCMV) as a model for HCMV to characterize the memory inflation response to wild-type MCMV (KP) and a latency-defective mutant (ΔM33stop), which lacks M33, an MCMV chemokine receptor homolog. M33 is essential for normal reactivation from latency and this was leveraged to determine whether reactivation in vivo contributes to T cell memory inflation. Methods Mice were infected with wild-type or mutant MCMV and T cell responses were analyzed by flow cytometry at acute and latent time points. Ex vivo reactivation and cytotoxicity assays were carried out to further investigate immunity and virus replication. Quantitative reverse-transcriptase polymerase chain reaction (q-RTPCR) was used to examine gene expression during reactivation. MHC expression on infected cells was analyzed by flow cytometry. Finally, T cells were depleted from latently-infected B cell-deficient mice to examine the in vivo difference in reactivation between wild-type and ΔM33stop. Results We found that ΔM33stop triggers memory inflation specific for peptides derived from the immediate-early protein IE1 but not the early protein m164, in contrast to wild-type MCMV. During ex vivo reactivation, gene expression in DM33stop-infected lung tissues was delayed compared to wild-type virus. Normal gene expression was partially rescued by substitution of the HCMV US28 open reading frame in place of the M33 gene. In vivo depletion of T cells in immunoglobulin heavy chain-knockout mice resulted in reactivation of wild-type MCMV, but not ΔM33stop, confirming the role of M33 during reactivation from latency. Further, we found that M33 induces isotype-specific downregulation of MHC class I on the cell surface suggesting previously unappreciated roles in immune evasion. Discussion Our results indicate that M33 is more polyfunctional than previously appreciated. In addition to its role in reactivation, which had been previously described, we found that M33 alters viral gene expression, host T cell memory inflation, and MHC class I expression. US28 was able to partially complement most functions of M33, suggesting that its role in HCMV infection may be similarly pleotropic.